THE ROLE OF ACCOUNTING UNDERSTANDING IN PREPARING FINANCIAL REPORTS BASED ON EMKM FINANCIAL ACCOUNTING STANDARDS TO INCREASE BUSINESS INCOME - Dewi, Nur Fitri (Jaksya: Jurnal Akuntansi Syariah, 2024)
The growth of MSMEs in Indonesia is currently experiencing rapid changes. However, many MSME players, including those in Alang - Alang Lebar District, Palembang, South Sumatra, do not fully understand the importance of accounting understanding and preparing financial reports based on EMKM Financial Accounting Standards in their business. This research aims to assess how accounting understanding influences the preparation of financial reports based on EMKM Financial Accounting Standards and subsequently has an impact on MSME business income in Alang-Alang Lebar, Palembang. The research focuses on MSMEs in the area, with data collected from 100 samples through questionnaires. Data analysis using SPSS 27.00 using t test and Path Analysis. The findings show that accounting understanding has a positive effect on preparing financial reports based on EMKM Financial Accounting Standards. Understanding accounting also has a positive effect on business income, both directly and indirectly through preparing financial reports based on EMKM Financial Accounting Standards. Apart from that, preparing financial reports based on EMKM Financial Accounting Standards has a direct effect on business income. These findings can provide valuable insight for MSMEs in developing strategies, especially in increasing understanding of accounting in order to improve the preparation of financial reports so that they can increase business income for MSMEs in Alang - Alang Lebar.